Coagulopathy Spectrums in COVID-19 Patients at A Tertiary Care Diagnostic Center in Pakistan - Ali, Intzar; Robert, Helen Mary; Andleeb, Komal; Rana, Noman Anjum; Asghar, Muhammad Bilal; Shahid, Muhammad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the coagulopathy spectrums in patients with COVID-19 infection at a tertiary care diagnostic center in Pakistan.Study Design: Cross-sectional studyPlace and Duration of Study: Pathology Department, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Apr to Sep 2021.Methodology: A total of 196 patients fulfilling the selection criteria were enrolled after taking written informed consent and investigations to assess coagulation parameters were carried out such as complete blood count, PT, APTT and D-Dimers and findings were subjected to statistical analysis.Results: Mean age of the patients was 35.20±0.98 years. Platelet count was found to be normal in 152(77.6%) patients and low in 44(22.4%) patients, PT was normal in 182(92.9%) patients and prolonged in 14(7.1%) patients, APTT was normal in 152(77.6%) patients and prolonged in 44(22.4%) and D-Dimers was raised in 87(44.4%) patients and was raised in 109(55.6%) patientsConclusion: The commonest coagulation pathology was D-Dimers i.e. in 52.6% patients, followed by APTT and platelet count in COVID-19 patients of varying severity.